2002
DOI: 10.1016/s1535-6108(02)00153-8
|View full text |Cite
|
Sign up to set email alerts
|

MMP9 induction by vascular endothelial growth factor receptor-1 is involved in lung-specific metastasis

Abstract: The molecular mechanism of tissue-specific metastasis in tumors endogenously expressing members of the vascular endothelial growth factor (VEGF) family is not yet clear. Here we demonstrate that MMP9 is specifically induced in premetastatic lung endothelial cells and macrophages by distant primary tumors via VEGFR-1/Flt-1 tyrosine kinase (TK) and that it significantly promotes lung metastasis. In a genetic approach using mice, suppression of MMP9 induction by deletion of either VEGFR-1TK or MMP9 markedly reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

29
655
0
16

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 811 publications
(700 citation statements)
references
References 48 publications
29
655
0
16
Order By: Relevance
“…Members of the VEGF family's angiogenic signals are mainly mediated by activation of the structurally related homologous tyrosine kinase receptors, VEGFR-1 and VEGFR-2. A previous study has shown that blocking VEGFR-1 activity reduces lung metastasis [25]. These results are consistent with the discovery of increased amounts of VEGFR-1 in the serum of the mouse lung cancer model compared to the matched control found in this study.…”
Section: Resultssupporting
confidence: 93%
“…Members of the VEGF family's angiogenic signals are mainly mediated by activation of the structurally related homologous tyrosine kinase receptors, VEGFR-1 and VEGFR-2. A previous study has shown that blocking VEGFR-1 activity reduces lung metastasis [25]. These results are consistent with the discovery of increased amounts of VEGFR-1 in the serum of the mouse lung cancer model compared to the matched control found in this study.…”
Section: Resultssupporting
confidence: 93%
“…Transforming growth factor-b is a potent growth inhibitor of normal epithelial cells, but also fosters tumor formation during later stages of tumorigenesis (Wakefield and Roberts, 2002). Transforming growth factor-b enhances the expression of MMP9, which plays significant roles during the dissemination and growth of cancer cells (Itoh et al, 1999;Coussens et al, 2000;Hiratsuka et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…This realization was the basis of the "Seed and soil" theory. This theory was expanded upon when tumors were shown to directly enhance the seeding of circulating cells in the lungs [299], suggesting that the tumor can modulate the "soil" to make it more compatible with the "seed". Later studies have shown the direct involvement of bone marrow derived VEGFR1 + progenitor cells [300,301] in generating the pre-metastatic niche that is more receptive toward incoming tumor cells.…”
Section: Neutrophils In Pre-metastatic Organs -The "Seed and Soil" Hymentioning
confidence: 99%